Anticonvulsant and neuroprotective effects of Rosa damascena hydro-alcoholic extract on rat hippocampus - Mansour Homayoun; Masoumeh seghatoleslam; Mojtaba Pourzaki; Reihaneh Shafieian; Mahmoud Hosseini; Alireza Ebrahimzadeh Bideskan (Mashhad University of Medical Sciences, 2015)
Objective: Previously, analgesic, hypnotic, and anticonvulsant effects have been suggested for Rosa damascena (R. damascena). In the present study, possible anti-seizure and neuro-protective effects of hydro-alcoholic extract of R. damascena has been investigated after inducing seizures in rats by pentylenetetrazole (PTZ). Materials and Methods: The rats were divided to five groups: (1) Control: received saline, (2) PTZ: 100 mg/kg, i.p., (3) PTZ-Extract 50 mg/kg(PTZ-Ext 50), (4) PTZ- Extract 100 mg/kg(PTZ-Ext 100), and (5) PTZ- Extract 200 mg/kg(PTZ-Ext 200) groups which were treated with 50, 100, and 200 mg/kg respectively of hydro-alcoholic extract of R. damascena for one week before PTZ injection. The animals were examined for electrocorticography (ECoG) recording and finally, the brains were removed for histological study. Results: The hydro-alcoholic extract of R. damascena significantly prolonged the latency of seizure attacks and reduced the frequency and amplitude of epileptiform burst discharges induced by PTZ injection. Moreover, all three doses of the extract significantly inhibited production of dark neurons in different regions of the hippocampus in the mentioned animal model. Conclusion: The present study showed that the hydro-alcoholic extract of R. damascena has anticonvulsant and neuroprotective effects. More investigations are needed to be done in order to better understand the responsible compound(s) as well as the possible mechanism(s).